THE QUEST FOR AN “INTEGRATED AND INTERCONNECTED” PARADIGM OF ISLAMIC STUDIES IN INDONESIA: A HISTORICAL ACCOUNT - Damanhuri Damanhuri (LP3M Universitas Sains Al Qur'an, 2021)
Method of Islamic studies has been a perpetually contested issue among scholars of Islam in both Western universities and Muslim academia as well. Taking the long-standing experience of Indonesian Islamic higher institution as a case study where contestations have been taking place, this paper aims at depicting the dynamic of Islamic studies from its early development to its contemporary and cutting-edge transformation. Drawing on Travelling Theory as its theoretical lens as well as employing Critical Discourse Analysis (CDA) as its method for analyzing the available textual data, this paper argues that an integrated and interconnected paradigm—instead of dualistic or dichotomist ones—of Islamic studies has been increasingly predominant among those engaging in Indonesian Islamic scholarship